A Theory of Foreign Exchange Speculation under Alternative Systems - Canterbery, E. Ray (Journal of Political Economy, 1971)
Is speculation destabilizing? This paper explores the question of whether free exchange rates result in more stability than optional systems. The study includes development of a linear, stable equilibrium model of a free rate system; examination of speculative-induced movements in market exchange rates; and simplification of mathematics to allow for speculative shifts under a narrow gold band and for full interaction between spot and foreign exchange rates. Conclusion: Speculators are stabilizers under absolutely free rates, relative stabilizers under a wide gold band, and destabilizers under a narrow gold band, a theory qualified by political problems and uncontrollable exogenous forces.